square root of 14 divided by the square root of 7 is the same as the square root of 14/7, so the answer is square root 2

((14)^(1/2))/((7)^(1/2))=(14/7)^(1/2)=2^(1/2)

Clarification: The question means: square root of 7 divided by square root of 14

So that's about 0.7071067 (square root of a half, not square root of 2).

🙏

0🤨

0😮

0😂

0Loading...

It is the square root of 14*14 = 196.

the square root of 14 = 3.7416573867739413855837487323165.

The square root of 14 is: ± 3.741657

Square root of 56 = Square root of (4 x 14) = (Square root of 4) x (Square root of 14) = 2 x (Square root of 14) The actual value would be 2 x 3.741 = 7.482

The square root of 196 is equal to 14.

The square root of 196 is 14.

13, is not the square root of 156, but the best i can give you is that 13 is the square root of 169 and 14 is the square root of 196.

The square root of 4 is 2, if you multiply that by the square root of 49, which is 7, you get 14.

square root of 203, or slightly over 14.

The square root of -196 is: 14 i

11.82

The square root of 196 is 14.

The square root of 196 is 14

The square root of 196 is 14 because 14 X 14 is equivalent to 196.14

2.3333

2 square root of 14

Approximately 9.8994949.

7*square root of 8.

14 (sqrt6)

The square root of 196 is 14

The square root of 14 is irrational. Three squared is 9, and four squared is 16; so square root of 14 is in-between 3 and 4.

It will be the square root of 14 which is 3.741657387

Neither. The square root of 14 is 3.7416573867739413855837487323165 while the cube root is 2.4101422641752299861283696676033

Natural numbers are those numbers used for counting. The square root of 14 is the irrational number 3.74165... . Therefore, the square root of 14 is not a natural number.

-2 and -3Check:(-2) + (-3) = -5(-2)(-3) = 6Thus -2 and -3 are not the required numbers. let's find them: x + y = -6xy = -5 y = -x -6x(-x - 6) = -5-x^2 - 6x = -5x^2 + 6x = 5x^2 + 6x + 9 = 5 + 9(x + 3)^2 = 14x + 3 = (+ & -)square root of 14x = -3 (+ & -)square root of 14x = -3 + square root of 14 or x = - 3 - square root of 14y = -x - 6y = 3 - square root of 14 - 6 or y = 3 + square root of 14 - 6y = -3 - square root of 14 or y = -3 + square root of 14Check:(-3 + square root of 14) + (-3 - square root of 14) = -6(-3 + square root of 14)(-3 - square root of 14) = -5 ?(-3)^2 - (square root of 14)^2 = -5 ?9 - 14 = -5Check also tow other numbers.